MEMBANGUN INDONESIA YANG KUAT DARI KELUARGA "INDONESIAN STRONG FROM HOME" - Faizal, Muhammad (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2015)
Indonesia is strongly built by the nation's next generation of powerfull and robust which is in the hands of early childhood. So to create the next generation a strong responsibility to be educated not only on formal institutional agencies. But the "home" is then termed "family" as an institution and the first main roles and functions that are crucial in the process of planting and establishment of the national character. Through character building in a family that includes aspects of maternal bonding, security compliance and fulfillment of physical and mental stimulation, as well as the implementation of appropriate parenting on children will build the next generation of Indonesian nation strong and resilient in facing the challenges of globalization in the future.